The Role of the Community in Preventing Bullying in Adolescent Children (12-18 Years) - Atik Setiawan Wahyuningsih; Neny Triana; Sutik; Vitaria Wahyu Astuti; Anik Nuridayanti; Erni Rahmawati; Erva Elli Kristanti (Journal Of Nursing Practice, 2024)
Background: Bullying is an aggressive act that is intentionally shown to teenagers, to disturb other teenagers who are considered weak or strange. Bullying behavior is considered by society as trivial behavior or normal behavior in every human life, in reality bullying behavior is abnormal, unhealthy and socially unacceptable behavior. Community participation is needed to prevent bullying. Purpose: The purpose of the study was to determine the role of society in preventing bullying in teenagers (aged 12-18 years). The research design was quasi-experimental, one group pretest-post test, the research population was 700 respondents with a sample of 42 respondents. The sampling technique was purposive sampling using the Slovin formula, with the inclusion criteria of people who were willing to be respondents, aged 19-60 years, able to read and write, cooperative, at the research location, and married. Exclusion criteria People who did not want to be respondents, were not at the location during the study, were sick. The study was conducted on March 21 - March 28, 2024, with the variable of community participation in preventing bullying, the research instrument used a questionnaire with a reliability coefficient value of Alpha Cronbach α > 0.5. Data were analyzed using the T-test. Data are presented in table form. Results: The results of the T-Test analysis obtained a p value <0.003, which means that there was a change in role after being given health education on bullying prevention. Conclusion: The role of the community is influenced by several factors in preventing bullying, namely gender, age, education, occupation, having received information about bullying prevention and sources of information.